1988
DOI: 10.1142/s0192415x88000121
|View full text |Cite
|
Sign up to set email alerts
|

Control of Preweaning Diarrhea in Piglets by Acupunture and Chinese Medicine

Abstract: Preweaning diarrhea in piglets is a very common disease. Even thought vaccination and antibiotics are used widely for controlling the disease nowadays, it is still a serious production problem. Therefore, the search for a new medication that is both cheaper and more effective is of major importance. During the last year, acupuncture and Chinese medicine have been evaluated for this purpose. The results are summarized as follows: 1) Oral administration of 0.5 g of Ko-ken-huang-lien-huang-chin-tang (pueraria, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0
1

Year Published

1991
1991
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 0 publications
0
6
0
1
Order By: Relevance
“…Acupuncture has been used in veterinary medicine to control diarrhea in pigs. 98 In humans, case reports have shown noted beneficial effects of acupuncture for infantile diarrhea. 99 Acupuncture at CV-12 has been used to treat patients with abdominal pain.…”
Section: Ibsmentioning
confidence: 99%
“…Acupuncture has been used in veterinary medicine to control diarrhea in pigs. 98 In humans, case reports have shown noted beneficial effects of acupuncture for infantile diarrhea. 99 Acupuncture at CV-12 has been used to treat patients with abdominal pain.…”
Section: Ibsmentioning
confidence: 99%
“…The present study showed that skin on the GV01 acupoint reveals tenderness and neurogenic inflammation in colonic inflammatory states, but not in normal healthy states.Key words: colitis, GV01, neurogenic inflammation.GV01 (Changqiang, Government Vessel 1), a single acupoint in the depression ventral to the base of the tail and dorsal to the anus, is one of the most effective acupoints for treating diarrhea in humans and animals [1][2][3][4][5]. In a recent study, we investigated whether large intestinerelated acupoints affect colonic motility in conscious dogs implanted with electrodes at the proximal colon.…”
mentioning
confidence: 99%
“…30 Nutmeg, fed daily to calves for 3 to 4 days after birth, was credited with the absence of diarrhea for 2 years on one farm. 77 Acupuncture was found to be equally effective as gentamicin for treatment of undifferentiated diarrhea in piglets 44 and was equal to neomycin for treatment of ETEC in piglets. 36 The use of probiotics has been advocated for prevention of diarrhea when fed before disease is present, and as an aid in enhancing recuperation if fed during convalescence.…”
Section: Other Treatmentsmentioning
confidence: 97%